MICROBIOLOGICAL CONTAMINATION of A HEMODIALYSIS CENTER WATER DISTRIBUTION SYSTEM - Montanari, Lilian Bueno; Sartori, Flavio Garcia; de Oliveira Cardoso, Miguel Jorge; Varo, Samuel Dutra; Pires, Regina Helena; Leite, Clarice Queico Fujimura [UNESP]; Prince, Karina [UNESP]; Gomes Martins, Carlos Henrique (Inst Medicina Tropical São Paulo, 2009)
The microbiological monitoring of the water used for hemodialysis is extremely important, especially because of the debilitated immune system of patients suffering from chronic renal insufficiency. To investigate the occurrence and species diversity of bacteria in waters, water samples were collected monthly from a hemodialysis center in upstate São Paulo and tap water samples at the terminal sites of the distribution system was sampled repeatedly (22 times) at each of five points in the distribution system; a further 36 samples were taken from cannulae in 19 hemodialysis machines that were ready for the next patient, four samples from the reuse system and 13 from the water storage system. To identify bacteria, samples were filtered through 0.22 mu m-pore membranes; for mycobacteria, 0.45 mu m pores were used. Conventional microbiological and molecular methods were used in the analysis. Bacteria were isolated from the distribution system (128 isolates), kidney machine water (43) and reuse system (3). Among these isolates, 32 were Gram-positive rods, 120 Gram-negative rods, 20 Gram-positive cocci and 11 mycobacteria. We propose the continual monitoring of the water supplies in hemodialysis centers and the adoption of effective prophylactic measures that minimize the exposure of these immunodeficient patients to contaminated sources of water.
Keywords: Dialysis; Water; Microbiological contamination; Water treatment; Dialysis fluid quality; Bacterial count